Single-cell transcriptomic analysis in two patients with rare systemic autoinflammatory diseases treated with anti-TNF therapy - Hua, Yichao; Wu, Na; Miao, Junke; Shen, Min (Frontiers in Immunology, 2023)
Systemic autoinflammatory diseases (SAIDs) are a group of rare diseases characterized by recurrent or continuous inflammation, typically accompanied by genetic variants. Good responses to anti-TNF therapy were observed in SAIDs patients. However, the mechanisms underlying the disease flare and the response to TNF blocking therapy have not been fully elucidated. Here, single-cell RNA sequencing technology was used to describe the transcriptomic profile of PBMCs and PMNs in two SAIDs patients both before and after anti-TNF treatment. Interferon responses are involved in the disease flare. After anti-TNF therapy, clinical symptoms were alleviated while TNF and IL-1 were unexpectedly increased, indicating that these inflammatory cytokines are not positively correlated with disease activity. Trajectory analysis showed that inhibition of macrophage differentiation, rather than reduction of the inflammatory cytokines, as the potential mechanism of anti-TNF treatment response in SAIDs.